Perbandingan Implementasi Manajemen Pengetahuan pada Berbagai Industri - Tommy Wijaya Sagala; Eliyah Acantha Manapa; Valian Yoga Pudya Ardhana; Godfried Lewakabessy (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Customer knowledge is a valuable asset, and gathering, managing, and sharing customerknowledge can be a useful competitive activity for organizations. Successful knowledgepartnerships with essential and valuable customers can strengthen business performance andcreate an absolute competitive advantage that is difficult for competitors to emulate. Inconsumer knowledge management, companies often experience significant obstacles orconstraints so that sometimes many companies prevent them from managing consumerknowledge. The company or organization depends on consumers who do not need tounderstand the industrial field of the company or organization. This paper discusses thecomparison of the application of customer knowledge management in various industries.Research findings that all organizations must apply the three essential components ofcustomer-related knowledge within the underlying conceptual framework. Three basiccomponents of customer-related knowledge within a basic conceptual framework: knowledgefor customers, knowledge of customers, and customer knowledge, cannot be eliminated. Thisproves that the compatibility with previous studies. In fact, to succeed, they must be applied sothat it is of value to the company. Implementation of the framework can present a greatopportunity for the organization or company to make new products so that this will improvethe performance of the company or organization and maintain the continuity of the companyor organization.